2014
DOI: 10.1016/j.enbuild.2014.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Multi-objective optimization for building retrofit: A model using genetic algorithm and artificial neural network and an application

Abstract: Page 2 of 46 A c c e p t e d M a n u s c r i p t 2 Retrofitting of existing buildings offers significant opportunities for improving occupants' comfort and well-being, reducing global energy consumption and greenhouse gas emissions. This is being considered as one of the main approaches to achieve sustainability in the built environment at relatively low cost and high uptake rates. Although a wide range of retrofit technologies is readily available, methods to identify the most suitable set of retrofit actions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
170
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 407 publications
(172 citation statements)
references
References 21 publications
1
170
0
1
Order By: Relevance
“…These problems may be tackled using multi-objective optimization models, in which the set of potential alternatives is implicitly defined by constraints defining a feasible region and multiple objective functions are optimized, or multi-criteria decision analysis, in which the alternatives are explicitly known apriori to be appraised by (qualitative and/or quantitative) multiple criteria. Simulation techniques are also used to deal with this problem, in general focusing on particular aspects rather than following a global approach (Asadi, Silva, Antunes, Dias, & Glicksman, 2014;Caccavelli & Gugerli, 2002;Chidiac, Catania, & Morofsky, 2011a;Chidiac, Catania, Morofsky, & Foo, 2011b;Diakaki, Grigoroudis, & Kolokotsa, 2008;Doukas, Nychtis, & Psarras, 2009;Soares et al, in press;Verbruggen, Al Marchohi, & Janssens, 2011).…”
Section: Risk Uncertainty and Real Options In Energy Retrofit Of Buimentioning
confidence: 99%
See 1 more Smart Citation
“…These problems may be tackled using multi-objective optimization models, in which the set of potential alternatives is implicitly defined by constraints defining a feasible region and multiple objective functions are optimized, or multi-criteria decision analysis, in which the alternatives are explicitly known apriori to be appraised by (qualitative and/or quantitative) multiple criteria. Simulation techniques are also used to deal with this problem, in general focusing on particular aspects rather than following a global approach (Asadi, Silva, Antunes, Dias, & Glicksman, 2014;Caccavelli & Gugerli, 2002;Chidiac, Catania, & Morofsky, 2011a;Chidiac, Catania, Morofsky, & Foo, 2011b;Diakaki, Grigoroudis, & Kolokotsa, 2008;Doukas, Nychtis, & Psarras, 2009;Soares et al, in press;Verbruggen, Al Marchohi, & Janssens, 2011).…”
Section: Risk Uncertainty and Real Options In Energy Retrofit Of Buimentioning
confidence: 99%
“…The algorithm proposed was called Genetic Algorithm for Energy Efficiency in Buildings (GAEEB) and its pseudo-code is presented in Algorithm 1. The GAEEB is based on NSGA-II (Deb, Pratap, Agarwal, & Meyarivan, 2002), which has been used to solve combinatorial problems in several areas as building retrofit (Asadi et al, 2014), optimal placement and sizing of distributed generation (Wanxing, Ke-yan, Yuan, Xiaoli, & Yunhua, 2015) and generation expansion planning (Kannan, Baskar, McCalley, & Murugan, 2009), among many others.…”
Section: A Multi-objective Approachmentioning
confidence: 99%
“…The authors also state that volatile energy prices make postponing the retrofit measure the more profitable option. Taking into account three target parameters, namely energy consumption, retrofit cost, and thermal discomfort hours, Asadi et al 201 showed that genetic algorithms combined with artificial neural networks solve the optimization problem much faster than conventional approaches. The optimization results can be used to evaluate the impact of individual retrofit measures and to facilitate decision making in a retrofit project.…”
Section: Building Retrofitmentioning
confidence: 99%
“…Equation (25) reflects the construction delay. Equation (26) denotes the idle penalty due to construction which reflects the value of the building. Equation (27) presents a single construction constraint for each floor and construction material.…”
Section: Model Formulationmentioning
confidence: 99%
“…Malatji et al [10] suggested a multi-objective optimization model for maximizing energy savings in buildings, and minimizing the return period of the initial budget with the genetic algorithm. Asadi et al [26] proposed an energy consumption prediction model through an artificial neural network and genetic algorithm to solve the multi-objective optimization problem.…”
Section: Related Literaturesmentioning
confidence: 99%